KESANTUNAN BERBAHASA PADA KOLOM KOMENTAR DI DALAM AKUN FACEBOOK “INFO CEGATAN WILAYAH PONOROGO (ICWP)” - Artalisananda, Bima Devisa; Suprayitno, Edy; Astuti, Cutiana Windri (STKIP PGRI Ponorogo Press, 2021)
Research on politeness discusses the use or application of language (language use) in a particular language community. Speech society is defined as people who have various backgrounds in the social and cultural conditions that surround them. This study discusses politeness in terms of the meaning and function of speech. The purpose of this research is to describe the form of wisdom maxims, suitability maxims, and conclusions maxims found in the comments column on the Facebook group in the “Info Cegatan Wilayah Ponorogo”. This type of research was using descriptive data with qualitative approach. Descriptive data in this study were in the form of written words in the comments column collected from the field, based on existing facts. The results of the analysis conducted by the researcher, there were three types of maxims, namely tact maxims, agreement maxims, and approbation maxims.